Design of circular composite beams with a different concrete core considering the effect of concrete in tension - Kvedaras, Audronis Kazimieras; Šaučiuvėnas, Gintas; Komka, Arūnas; Juozapaitis, Algirdas (Journal of Civil Engineering and Management, 2015)
Currently, the bending resistance of composite steel and concrete circular beams and beam-columns may be analysed assuming the interaction between the steel shell and concrete core but ignoring the behaviour of the part of the concrete core in tension. Some natural and numerical experiments show that an influence of this part of the concrete core on the total value of bending resistance of a composite member may be rather important. Therefore, this paper pre- sents the method developed for the design of hollow and solid concrete-filled steel tubular beams based on the test data. It takes into account an effect of the part of the concrete core in tension and gives a better agreement with test results than EC4 (EN 1994-1-1 2004). Also, the paper presents the results of carried out analytical, experimental and numerical investigations of the hollow centrifuged and solid concrete-filled steel tubular beams.